Nutritional and Functional Composition of Barley Varieties From Legambo District, Ethiopia - Yalew Yiblet; Worku Misganaw; Endale Adamu (The Scientific World Journal)
In agriculture, barley holds significant importance as a vital crop with multiple uses. It provides a variety of advantages, including weed suppression, erosion management, nutrient recycling, and improved soil structure. The nutritional and functional composition of barley varieties’ samples were analyzed using AOAC methods. The moisture content of the samples ranged from 7.3% to 12.8%, while the ash content varied from 0.5% to 13%. The crude fiber content ranged from 0.5% to 1.5%, and the crude protein content ranged from 0.73% to 3.4%. Furthermore, the crude fat content ranged from 0.11% to 0.8%. The carbohydrate content of the samples were found to be between 69.5% and 82.5%, with an energy value ranging from 338.2 to 382.02 kcal/100 g. In terms of mineral content, the samples exhibited varying levels of calcium (310–670 mg/100 g), iron (34.9–65 mg/100 g), zinc (8.9–16 mg/100 g), and magnesium (Mg) (520–1122 mg/100 g). In addition, the range of the total phenolic content was 1.2 to 3.1 mg/100 g, while the range of the total flavonoid content was 0.41 to 0.55 mg/100 g. Therefore, barley, a selenium-rich food, acts as an antioxidant, protecting cells from free radical damage, reducing inflammation, and reducing the risk of chronic illnesses. The highest content of stearic acid (3.4 g/100 g) followed by myristic acid (2.6 g/100 g) were found in barley varieties. Barley amino acids are essential nutrients for various biological processes, muscle repair, immunological system function, neurotransmitter generation, and detoxification.